Digital Storytelling Strategy and Visual Branding in Enhancing Brand Resonance in Footwear Startupreneur - Sausan Raihana Putri Junaedi; Ninda Lutfiani; Tuti Nurhaeni; Natalie Bibils (ADI Journal on Recent Innovation (AJRI), 2026)
The rapid development of digital technology has encouraged startupreneur footwear businesses to implement innovative digital branding strategies to attract and retain consumers. This study aims to analyze the influence of digital storytelling and visual branding on brand resonance in startupreneur footwear businesses. A quantitative approach was employed, with data collected through questionnaires, social media observation, and literature studies. A total of 100 respondents were selected using purposive sampling. Data analysis was conducted using SmartPLS to evaluate the measurement and structural models. The findings indicate that digital storytelling and visual branding have a positive and significant influence on brand resonance. Digital storytelling has a positive and significant effect on brand resonance (β = 0.49, t = 5.27), while visual branding also has a positive and significant effect (β = 0.38, t = 3.90). Together, digital storytelling and visual branding explain 65% of the variance in brand resonance (R² = 0.65). Digital storytelling through authentic and emotionally engaging content increases consumer engagement and emotional connection with the brand. Meanwhile, visual branding through consistent visual identity, color usage, logo, and social media design strengthens brand recognition and consumer trust. The integration of digital storytelling and visual branding can enhance customer loyalty, repeat purchase intention, and Electronic Word of Mouth (e- WOM). Furthermore, Instagram and TikTok play important roles in supporting digital branding strategies for footwear businesses. This study contributes to digital marketing and branding strategies while supporting the Sustainable Development Goals (SDGs), particularly SDG 8 and SDG 9.